A Proposal for the Analysis of Female Stereotypes in Reggaeton Videoclips: Case Study of the Four most Viewed Videos in 2018 on YouTube - Monedero Morales, Carmen del Rocío (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2020)
The representation of women in music is an object of research little developed academically and much less in contemporary and popular musical styles such as urban music. This text proposes the analysis of stereotypes of women as a character in international success reggaeton songs performed by men. For this purpose, content analysis sheets have been used primarily for the most viewed clips on youtube during 2018. The design of the sheet is fed by other research previously carried out by experts in the field, to finally synthesize the information in three blocks: the first two, coded to obtain quantitative results and the third, to collect qualitative data.